The semiotic significance of monetary design in historical context - Yue Xiang Lin (Clío, 2025)
This article analyses the evolution of currency design as a means of communication through semiotic, cultural, and historical approaches. Case studies from China, the US, Japan, and Singapore reveal how design reflects national identity, historical memory, and cultural values. In antiquity, coins legitimised rulers; in the Middle Ages, they conveyed state and religious symbols. Since the eighteenth century, paper money incorporated economic and ideological messages. In the nineteenth and twentieth centuries, design grew more intellectualised, reflecting historical and cultural shifts. The study highlights modern trends, especially digitalisation, and shows how portraits, text, symbols, and colours convey stability, development, and power. China’s banknotes, for example, feature historical figures, landscapes, and technology as markers of national identity. The semiotic approach proves vital in understanding how currency communicates societal values. The findings are relevant for historians, cultural scholars, and economists, and offer insights for preserving symbolic meaning in digital currency formats.